Succinate is an inflammatory signal that induces IL-1 beta through HIF-1 alpha - MCGETTRICK-DILLON, ANNE; CORR, SINEAD; PALSSON, EVA; KELLY, VINCENT; O'NEILL, LUKE (My University, 2013)
Macrophages activated by the Gram-negative bacterial product lipopolysaccharide switch their core metabolism from oxidative phosphorylation to glycolysis. Here we show that inhibition of glycolysis with 2-deoxyglucose suppresses lipopolysaccharide-induced interleukin-1β but not tumour-necrosis factor-α in mouse macrophages. A comprehensive metabolic map of lipopolysaccharide-activated macrophages shows upregulation of glycolytic and downregulation of mitochondrial genes, which correlates directly with the expression profiles of altered metabolites. Lipopolysaccharide strongly increases the levels of the tricarboxylic-acid cycle intermediate succinate. Glutamine-dependent anerplerosis is the principal source of succinate, although the 'GABA (γ-aminobutyric acid) shunt' pathway also has a role. Lipopolysaccharide-induced succinate stabilizes hypoxia-inducible factor-1α, an effect that is inhibited by 2-deoxyglucose, with interleukin-1β as an important target. Lipopolysaccharide also increases succinylation of several proteins. We therefore identify succinate as a metabolite in innate immune signalling, which enhances interleukin-1β production during inflammation.
PUBLISHED
Keywords: tricarboxylic-acid cycle intermediate succinate; tricarboxylic-acid cycle intermediate succinate; Immunology, Inflammation & Infection